Delayed Increase in Blood Lactate Concentration after a Short, Intense CrossFit® Workout - Meier, Nicole; Thaden, Thomas; Schmidt, Annette (Archives of Clinical and Medical Case Reports, 2021)
CrossFit®, the most successful concept for high-intensity interval training (HIIT), consists of constantly varied training loads und and is usually performed as Workouts Of the Day (WOD) with a length of 6 minutes and more. However, regular CrossFit® training concepts also include shorter WODs, the physiology responses have rarely been investigated yet. In this Study we wanted to analyze the blood lactate concentration (LAC) after ultra-short, high-intensive CrossFit® workout and investigate whether the kinetics of LAC is related to heart rate (HR) or the ratings of perceived exertion measured by borg-scale (borg-RPE). To determine whether CrossFit® workouts induces increased LAC levels after the exercise load, ten participants (n= 10; 8 males; 2 females) volunteered in the study. The participants completed a WOD consisting of 30/20 Calories AirBike and ten repetitions Devil Press with 10 kg/5 kg dumbbell (men/female). LAC, HR, and borg-RPE were measured immediately after, until 12 min after the WOD. The lactate turning points (LTP1 /LTP2) were previously determined using a bicycle ergometer performance diagnostic. The LAC values increased immediately after the WOD by 2.3 ± 1.4 fold (mean ± SD) of the LTP2 up to the maximum by 3.9 ± 0.96- fold during the post-workout observation period.